Knee Instability and Basic and Advanced Function Decline in Knee Osteoarthritis. Issue 8 (August 2015) - Sharma, Leena; Chmiel, Joan S.; Almagor, Orit; Moisio, Kirsten; Chang, Alison H.; Belisle, Laura; Zhang, Yunhui; Hayes, Karen W.
<x xml:space="preserve">Abstract</x> Objective Manifestations of instability in knee osteoarthritis (OA) include low overall knee confidence, low confidence that the knees will not buckle, buckling, and excessive motion during gait. Confidence and buckling may particularly influence activity choices, contributing to events leading to disability. Buckling is more likely to affect advanced than basic functional tasks. In this prospective longitudinal study, we tested the hypothesis that overall knee confidence, buckling confidence, buckling, and frontal plane motion during gait are associated with advanced 2‐year function outcomes in persons with knee OA. Methods Persons with knee OA were queried about overall knee confidence (higher score = worse confidence), buckling confidence, and knee buckling, and underwent quantitative gait analysis to quantify varus–valgus excursion and angular velocity. Physical function was assessed using the Late‐Life Function and Disability Instrument Basic and Advanced Lower Extremity Domain scores. Logistic regression was used to evaluate the relationship between baseline instability measures and baseline‐to‐2‐year function outcome, adjusting for potential confounders. Results The sample was comprised of 212 persons (mean age 64.6 years, 76.9% women). Buckling was significantly associated with poor advanced function outcome (adjusted odds ratio [OR] 2.08, 95% confidence interval [95% CI] 1.03–4.20) but not basic function outcome. Overall knee confidence was significantly associated with advanced outcome (adjusted OR 1.65, 95% CI 1.01–2.70), while associations between buckling confidence and both outcomes approached significance. Neither varus–valgus excursion nor angular velocity during gait was associated with either outcome. Conclusion Knee buckling and low knee confidence were each associated with poor 2‐year advanced function outcomes. Current treatment does not address these modifiable factors; interventions to address them may improve outcome in knee OA.